2021
DOI: 10.1371/journal.pone.0250779
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for insomnia and sleep-disordered breathing in military communities: A meta-analysis

Abstract: Background Many reviews and meta-analyses had been conducted to investigate risk factors for sleep disorders in the general population. However, no similar research has been performed in the military population though insomnia and sleep-disordered breathing are quite prevalent in that population. Objectives To investigate risk factors for insomnia and sleep-disordered breathing in military personnel. Methods A systematic literature search was performed from inception to March 2021 and 6496 records were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…These differences could be due to the times at which the surveys were measured, the characteristics of the population, and the difference in the instruments used. This may also be different due to particular factors in the military, such as post-traumatic stress disorder, increased risk of physical injury, and experience of traumatic events [ 21 ]. In addition, our result is higher than those reported in U.S. military members, who showed a prevalence of 11.5%, 16.3%, and 19.9% in pre-deployment military, veterans, and active military from three major services, respectively [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences could be due to the times at which the surveys were measured, the characteristics of the population, and the difference in the instruments used. This may also be different due to particular factors in the military, such as post-traumatic stress disorder, increased risk of physical injury, and experience of traumatic events [ 21 ]. In addition, our result is higher than those reported in U.S. military members, who showed a prevalence of 11.5%, 16.3%, and 19.9% in pre-deployment military, veterans, and active military from three major services, respectively [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result coincides with a study that reported that having a history of head injury and mental health outcomes increases the probability of developing insomnia [ 43 ]. Likewise, a systematic review showed that the combined outcome of four comorbidities increases the risk in active duty personnel by up to 53% [ 21 ]. This finding could be explained by the fact that sleep disorders such as insomnia may be due to a psychiatric disorder and may also predispose a serving military member to develop post-traumatic stress disorder and other psychiatric conditions [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying sociodemographic risk factors for developing sleep disorders are critical because officials can know beforehand which populations are at a higher risk for certain sleep disorders and implement early interventions for those at risk ( 13 ). The effects of sociodemographic factors, such as age, sex, alcohol intake, and race on sleep, have been studied in the military population ( 4 , 14–16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factors considered in the studies, with statistical significance, were: age, weight, height, body mass index (BMI), smoking history, neck circumference, abdominal circumference. Numerous reviews and meta-analyses have been conducted to investigate risk factors for sleep disorders in the general population 5,6 .…”
Section: Introductionmentioning
confidence: 99%